Webinar: Cómo citar y organizar tu bibliografía usando el gestor bibliográfico Mendeley - Silva, Aline (2021)
Aline Silva (Brasil) - Expositora / Jeyhson Vicharra (Perú) - Moderador / Rubén Luis (Perú) - Moderador